Validation of a videogrammetry technique for analysing American football helmet kinematics. Issue 5 (2nd September 2020) - Bailey, Ann; Funk, James; Lessley, David; Sherwood, Chris; Crandall, Jeff; Neale, William; Rose, Nathan
ABSTRACT: Professional American football games are recorded in digital video with multiple cameras, often at high resolution and high frame rates. The purpose of this study was to evaluate the accuracy of a videogrammetry technique to calculate translational and rotational helmet velocity before, during and after a helmet impact. In total, 10 football impacts were staged in a National Football League (NFL) stadium by propelling helmeted 50th percentile male crash test dummies into each other or the ground at speeds and orientations representative of concussive impacts for NFL players. The tests were recorded by experienced sports film crews to obtain video coverage and quality typically available for NFL games. A videogrammetry procedure was used to track the position and rotation of the helmet throughout the relevant time interval of the head impact. Compared with rigidly mounted retroreflective marker three dimensional (3-D) motion tracking that was concurrently collected in the experiments, videogrammetry accurately calculated changes in translational and rotational velocity of the helmet using high frame rate (two cameras at 240 Hz) video (7% and 15% error, respectively). Low frame rate (2 cameras at 60 Hz) video was adequate for calculating pre-impact translational velocity but not for calculating the translational or rotational velocity change of the helmet during impact.